Lower Limb Kinematics and Dynamic Postural Stability in Anterior Cruciate Ligament-Reconstructed Female Athletes - Delahunt, Eamonn (National Athletic Trainers Association, 2013)
CONTEXT: Deficits in lower limb kinematics and postural stability are predisposing factors to the development of knee ligamentous injury. The extent to which these deficits are present after anterior cruciate ligament (ACL) reconstruction is still largely unknown. The primary hypothesis of the present study was that female athletes who have undergone ACL reconstruction and who have returned to sport participation would exhibit deficits in dynamic postural stability as well as deficiencies in hip- and knee-joint kinematics when compared with an age-, activity-, and sex-matched uninjured control group. OBJECTIVE: To investigate dynamic postural stability as quantified by the Star Excursion Balance Test (SEBT) and simultaneous hip- and knee-joint kinematic profiles in female athletes who have undergone ACL reconstruction. DESIGN: Descriptive laboratory study. SETTING: University motion-analysis laboratory. PATIENTS OR OTHER PARTICIPANTS: Fourteen female athletes who had previously undergone ACL reconstruction (ACL-R) and 17 age- and sex-matched uninjured controls. INTERVENTION(S): Each participant performed 3 trials of the anterior, posterior-medial, and posterior-lateral directional components of the SEBT. MAIN OUTCOME MEASURE(S): Reach distances for each directional component were quantified and expressed as a percentage of leg length. Simultaneous hip- and knee-joint kinematic profiles were recorded using a motion-analysis system. RESULTS: The ACL-R group had decreased reach distances on the posterior-medial (P < .01) and posterior-lateral (P < .01) directional components of the SEBT. During performance of the directional components of the SEBT, ACL-R participants demonstrated altered hip-joint frontal-, sagittal-, and transverse-plane kinematic profiles (P < .05), as well as altered knee-joint sagittal-plane kinematic profiles (P < .05). CONCLUSIONS: Deficits in dynamic postural stability and concomitant altered hip- and knee-joint kinematics are present after ACL reconstruction and return to competitive activity. The extent to which these deficits influence potential future injury is worthy of investigation.